Plant names of Finno-Ugric Languages Motivated by Plant Parts Form and Their Equivalents in the English language: Comparative Analysis - E. G. Galitsyna (Научный диалог, 2018)
The article is devoted to the comparison of plant names of the Finno-Ugric and English languages. The basis for the analysis are the plant names of the Finnish language and Karelian dialects, including the characteristic of the form of any part of the plant. The comparison of these plant names with the names of the same plants in the English language is made. The article analyzes the names of 8 plants, such as bindweed (Convolvulus L.), reedmace (Typha L.), club moss (Lycopodium clavatum L.), marigold (Calendula L.), garlic (Allium sativum L.), couch grass (Elytrigia Desv.), fern (fam. Polypodiaceae), fuchsia (Fuchsia L.). In each case, information about the motivation of the plant names is given and nominative features that determine the names are pointed out. According to the presented material, Finno-Ugric and English plant names can be motivated by the form of stems, inflorescences, fruits, shoots, leaves and flowers of plants. Attention is also paid to the etymology of the analyzed lexical units. The author considers the plant names of the English language in the dynamic aspect, indicating the names of the plants in Old, Middle and Modern English. On the basis of the material presented in the paper, conclusions are made about the similarity and difference in the nomination of the same natural objects in typologically different languages.